Use Mexico as a model - Abd Razak, Dzulkifli (2010)
PERHAPS it is only natural that some parties raised concerns about making History a must-pass subject. We may learn patriotism through the subject but, like loyalty, patriotism cannot be measured in any meaningful way through written examinations.